Pelatihan Pemanfaatan Chatgpt Untuk Meningkatan Produktivitas Dan Efisiensi Kerja Pada Pengurus Majelis Taklim Qur’ani Nurul Fattah - RR Roosita Cindrakasih; Diah Widyawati; Eni Saeni; Diana Tambunan; Adityo Fajar (CV Edujavare Publishing, 2026)
This community service program was implemented to improve digital literacy and work productivity among the administrators of the Nurul Fattah Qur'ani Taklim Assembly through training on the use of ChatGPT. Limited digital literacy among the administrators means that administrative efficiency, preparation of activity reports, and development of da'wah materials are still carried out manually, thus requiring significant time and energy. The implementation method adopted a participatory and applied approach, including interactive lectures, live demonstrations, guided practice, case studies, and pre-test and post-test evaluations. The training materials included an introduction to the concept of Artificial Intelligence, effective prompt engineering techniques, the use of ChatGPT for organizational administration, preparation of study materials and sermons, digital da'wah content, and ethics and responsibility in using AI. The training results showed a significant increase in participants' abilities to compile administrative documents, activity reports, proposals, and social media content more quickly, systematically, and professionally. In the long term, this program is expected to strengthen the foundation's modern, responsive, and digital technology-based governance. Thus, this activity not only contributes to improving the capacity of individual administrators but also supports the institutional transformation of the Nurul Fattah Qur'ani Taklim Assembly to be more adaptive to technological developments in the digital era.